Effects of Organic Manures and Npk on Growth and Protein Content of Okra (Abelmoschus Esculentus L. Moench) - Haque, F; Nishi, KN; Muslim, M; Rahman, MK (Journal of Biodiversity Conservation and Bioresource Management, 2021)
Effects of organic manures and NPK fertilizers on okra (Abelmoschus esculentus L. Moench) plants were evaluated in the net house of the Department of Soil, Water and Environment, University of Dhaka. The experiment was conducted in a randomized design replicated thrice with eighteen treatments involving eight organic manures along with NPK and without NPK fertilizers. Growth parameters viz. plant height, leaf number, leaf area and dry weight of root, stem, leaf and fruits were assessed. The highest height (132.5 cm), leaf number (21.5) and leaf area (412.09 cm2) were found in T9: Shebok 10 ton ha–1 treatment. The highest dry weight of a plant (40.6 g), number of fruits per plant (8) and dry weight of fruit per plant (3.71 g) were found in T11:N30P18K25 kg ha–1 plus ACI 5 ton ha–1 treatment. Maximum protein (25.37%) was achieved in T11, phosphorous (0.481 mg kg–1) in T14 and potassium (4.50 mg kg–1) in T13 treatment. Results varied significantly (p≤0.5). The overall best growth performance and protein content was observed in T9:Shebok 10 ton ha–1 and T11:N30P18K25 kg ha–1 plus ACI 5 ton ha–1 treatment, respectively. J. Biodivers. Conserv. Bioresour. Manag. 2020, 6(2): 83-88